ECO-LITERACY FIQH AL-BÃâAH DALAM HUKUM NASIONAL - Ahmad, Muhammad Mufid (Al-Jinayah: Jurnal Hukum Pidana Islam, 2016)
Abstract: The environmental crisis is a contemporary issue that draws the public attention. In Islam, protecting environment is an important aspect in preserving the existence of the macro life for all Godâs creatures without dwarfing one another. That is why in the environmental Islamic jurisprudence, protecting environment (hifz al-bÃ®âah) is equal as keeping religion (hifz al-dÃ®n), protecting soul (hifz al-nafs), maintaining intellect (hifz al-aql), maintaining descent (hifz al-nasl), and maintaining property (hifz al-mÃ¢l). The reason is that if the aspects of religion, life, intellect, lineage and property damaged, then the existence of humans on the environment becomes stained. Thus, al-Qaradawi made hifz al-bÃ®âah as an Islamic axiological study. From here, the effort to develop the epistemological basis of Islamic environmental jurisprudence becomes a necessity. Therefore, in this context, maqÃ¢shid al-syarÃ®âah (hifz al-bÃ®âah) is the main purpose of Islamic law. It can also be an âapproachâ in reformulating the âanthropological and cosmological-based Islamic environmental jurisprudenceâ.Keywords: Fiqh al-bÃ®âah, hifz al-bÃ®âah, eco-literacy, national law.Â Abstrak: Krisis lingkungan merupakan isu kontemporer yang menyita perhatian publik. Dalam Islam, menjaga lingkungan merupakan aspek penting dalam upaya melestarikan eksistensi kehidupan makro bagi seluruh makhluk ciptaan Tuhan tanpa mengerdilkan satu sama lain. Itu sebabnya, doktrin Islam tentang fikih ramah lingkungan menyatakan bahwa menjaga lingkungan (hifz al-bÃ®âah) sama dengan menjaga agama (dÃ®n), jiwa (nafs), akal (aql), keturunan (nasl), dan harta (mÃ¢l). Rasionalitasnya adalah bahwa jika aspek-aspek agama, jiwa, akal, keturunan dan harta rusak, maka eksistensi manusia di dalam lingkungan menjadi ternoda. Dengan demikian, al-QardÃ¢wÃ® menjadikan hifz al-bÃ®âah sebagai kajian aksiologi ilmu-ilmu keislaman. Dari sini, maka upaya pengembangan basis epistemology fikih lingkungan menjadi suatu keniscayaan. MaqÃ¢shid syarÃ®âah (hifz al-bÃ®âah) sebagai tujuan utama agama dapat menjadi âpisau analisisâ dalam mereformulasikan fikih lingkungan yang berbasis antropokosmis.Kata Kunci: Fiqh al-bÃ®âah, hifz al-bÃ®âah, eco-literacy, hukum nasional.